Hubungan Status Gizi dan Sindrom Metabolik dengan Kejadian Komplikasi Pasien Diabetes Mellitus Tipe 2 Rawat Jalan di RSUD Dr. Moewardi - Entika, Rieny Hutami, Ahmad Farudin, SKM, M.Si, Elida Soviana, S.Gz., M.Gizi (2017)
Background: Nutritional status is an easily measurable indicator to prevent complications in Diabetic Mellitus patients. Metabolic syndrome is a disorder of body functions which can be used as an indicator to determine the incidence of complications in Diabetic Mellitus patients. The incidence of complications in Diabetic Mellitus patients could deteriorate if not addressed immediately. Objective: To determine the association of nutritional status and metabolic syndrome to incidence of complication in Type 2 Diabetic Mellitus outpatient in RSUD Dr. Moewardi. Research Method: This is an observational research with cross sectional approach. A sample size of 35 people according to the inclusion criteria was selected using consecutive sampling method. Nutritional status was measured using the bathroom scales and microtoice whereas metabolic status was obtained from the results of laboratory tests and the measurement of waist circumference which then categorized according to the NCEP ATP III. All data were analyzed using Chi-Square and Fisher's Exact statistic test. Results: The results show the prevalence of overweight was 65,7%, underweight was 5.7%, and normal nutritional status was 28,6%. The prevalence of metabolic syndrome in Diabetes Mellitus patients was 48,6%. The prevalence of the incidence of complications in Diabetes Mellitus patients was 60%. The result of the analysis of the nutritional status variables p-value 0,312 obtained using Fisher's Exact and metabolic syndrome variables p-value 0,001 obtained using Chi-Square. Conclusion: There is an association between metabolic syndrome to incidence of complication in Type 2 Diabetic Mellitus patients and there is no association between nutritional status to incidence of complications in Type 2 Diabetic Mellitus patients. Keywords: Nutritional Status, Metabolic Syndrome, Incidence of Complications and Type 2 Diabetic Mellitus